2015
DOI: 10.5173/ceju.2015.552
|View full text |Cite
|
Sign up to set email alerts
|

Value of preoperative stone scoring systems in predicting the results of percutaneous nephrolithotomy

Abstract: IntroductionGuy's Stone Score and S.T.O.N.E. Nephrolithometry nomograms have been introduced for systematic and quantitative assessment of kidney stones.The aim of this study was to reveal the value of two scorings systems, Guy and S.T.O.N.E, most frequently used for predicting postoperative stone-free status prior to Percutaneous Nephrolithotomy (PCNL), in the prediction of postoperative results of PCNL.Material and methodsWe retrospectively examined patients who underwent PCNL. Preoperative abdominopelvic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
(31 reference statements)
0
29
2
Order By: Relevance
“…In a retrospective study by Kumsar et al . [ 16 ] to compare GSS and STONE score the stone-free rate was 90%, 96%, and 34% in GSS 1, 2, and 3 groups, respectively. Few authors have also found GSS based on CT scan to be effective in predicting success rate of PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study by Kumsar et al . [ 16 ] to compare GSS and STONE score the stone-free rate was 90%, 96%, and 34% in GSS 1, 2, and 3 groups, respectively. Few authors have also found GSS based on CT scan to be effective in predicting success rate of PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…Stone characteristics included the number of stones (detected via CT or MRI scan), staghorn (yes/no), stone location and stone burden. Stone surface area (stone burden) was calculated by the following formula: length × width × π × 0.25 [ 38 ]. In cases of multiple calculi, stone burden was defined as the sum of the surface area of each stone.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast Kumsar et al. found significant association between S.T.O.N.E score and SFR, operation time and Clavien complication scores [22]. In the recent study, a positive correlation was not found between S.T.O.N.E score and SFR, CR.…”
Section: Discussionmentioning
confidence: 68%
“…Kumsar et al. showed significant association between Clavien score, operation time and Guy score [22]. However the authors revealed no correlation between SFR and Guy score.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation